Resistance to myocardial infarction induced by heat stress and the effect of ATP-sensitive potassium channel blockade in the rat isolated heart - Joyeux, Marie (1998)
1. Heat stress (HS) is known to protect against myocardial ischaemia-reperfusion injury by improving mechanical dysfunction and decreasing necrosis. However, the mechanisms responsible for this form of cardioprotection remain to be elucidated. ATP-sensitive potassium (K(ATP)) channels have been shown to be involved in the delayed phase of protection following ischaemic preconditioning, a phenomenon closely resembling the HS-induced cardioprotection. The aim of this study was thus to investigate the role of K(ATP) channels in HS-induced protection of the isolated rat heart. 2. Twenty four hours after whole body heat stress (at 42°C for 15 min) or sham anaesthesia, isolated perfused hearts were subjected to a 15 min stabilization period followed by a 15 min infusion of either 10 μM glibenclamide (Glib), 100 μM sodium 5-hydroxydecanoate (5HD) or vehicle (0.04% DMSO). Regional ischaemia (35 min) and reperfusion (120 min) were then performed. 3. Prior heat stress significantly reduced infarct-to-risk ratio (from 42.4±2.4% to 19.4±2.9, P<0.001). This resistance to myocardial infarction was abolished in both Glib-treated (40.1±1.8% vs 42.3±1.8%) and 5HD-treated (41.2±1.8% vs 41.8±1.2%) groups. 4. The results of this study suggest that K(ATP) channel activation contributes to the cytoprotective response induced by heat stress.